Comprehensive assessment of the parameters of adaptive capacity and ecological stability of genotypes for winter garlic breeding - V. V. Skorina; Vit. V. Skoryna (Овощи России)
Relevance. Considering the regional peculiarities of the climate of Belarus in the cultivation of garlic, it is relevant to create varieties with high yields, environmental stability, winter hardiness and product quality in changing environmental conditions. The aim of the research is a comprehensive assessment of the genotypes of winter garlic according to the parameters of adaptability and the selection of the most stable samples among them.Materials and methods. The research was carried out on the experimental field of the Department of Fruit and Vegetable Growing of the Belarusian State Agricultural Academy, Gorki, Mogilev region during 2018-2022. The objects were collectible samples of winter garlic of various ecological and geographical origin. Field and laboratory experiments were carried out using generally accepted methods and guidelines. Meteorological conditions during the years of research differed both in temperature indicators and the amount of precipitation, which contributed to an objective assessment of the studied samples according to a complex of economically useful signs and the determination of parameters of adaptive capacity and environmental stability.Results. As a result a comprehensive assessment of the parameters of adaptive capacity and environmental stability of genotypes was given. The results of the data obtained when studying the reaction of genotypes to the medium showed that 44% (11) of the 25 genotypes were unstable with a positive reaction to the medium, and 56% (14) were stable. Studies have revealed diversity among genotypes in terms of the main parameters of adaptability, including SCGi. The analysis of the data obtained makes it possible to determine the common properties of genotypes with a high level of the SCGi parameter or the differences between them and other issues of the specificity of genotypes with a different combination of adaptability and stability parameters. The specificity consists in a combination of maximum values of the level of parameters Xi, OASi, CACi, with significant responsiveness to improving environmental conditions (bi) and average relative stability. A genotype with a low value of the SCGi parameter can be highly stable and serve as a source of this property. In the opposite case, it can be used as a parent form to transmit to the offspring the properties of productivity in combination with stability.